2020
DOI: 10.1111/ajad.13084
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine Medication for Opioid Use Disorder: A Study of Factors Associated With Postpartum Treatment Retention

Abstract: Background and Objectives: The factors associated with medication for opioid use disorder (MOUD) treatment retention among pregnant women with opioid use disorder (OUD) are largely unknown. This study sought to characterize factors associated with postpartum treatment retention. Methods: A retrospective chart review from 2014 to 2017 was conducted among women with OUD in pregnancy treated with buprenorphine. Women were assigned to the treatment retention group if they attended an appointment within 10 to 14 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Risk factors for MOUD treatment non-retention during pregnancy and the postpartum period include non-White race, younger age, alcohol and drug use/use disorders, missing healthcare appointments, and MOUD-related factors, such as lower duration or dose of treatment prior to delivery ( 9 12 ). Qualitative studies have identified additional retention barriers of parenting stress, mood disorders, discrimination for prenatal substance use, shame about having a substance-exposed infant, lack of autonomy over treatment decisions, and scrutiny from child welfare ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for MOUD treatment non-retention during pregnancy and the postpartum period include non-White race, younger age, alcohol and drug use/use disorders, missing healthcare appointments, and MOUD-related factors, such as lower duration or dose of treatment prior to delivery ( 9 12 ). Qualitative studies have identified additional retention barriers of parenting stress, mood disorders, discrimination for prenatal substance use, shame about having a substance-exposed infant, lack of autonomy over treatment decisions, and scrutiny from child welfare ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Randomized trials of both buprenorphine and methadone have found no relationship between dose and adverse outcomes such as total morphine needed to treat NOWS, neonatal hospital stay, duration of NOWS treatment, estimated gestational age at delivery, 5-minute APGAR, or newborn anthropometric measurements [ 21 , 22 ]. Rather, higher buprenorphine doses are associated with higher levels of treatment retention during pregnancy and postpartum [ 20 , 23 , 24 ]. Although initial dose did not predict discharge dose, the more clinically significant outcomes are number of dose adjustments and length of stay, as these could influence patient withdrawal, reflect more complicated inductions, and potentially contribute to patients leaving against medical advice due to the difficulty and discomfort of reaching a stable dose.…”
Section: Discussionmentioning
confidence: 99%
“…High rates of incarceration are seen elsewhere in the literature, with 29.3% of patients in one study having current legal involvement and 23% lost to follow up. Those lost to follow up were more likely to have legal involvement 30 days prior to cohort enrollment [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supportive, nonjudgmental relationships with service providers can be motivators for persons to make positive changes in their substance use during pregnancy (Ray-Griffi th et al, 2021). Nurses who provide unbiased guidance and support, particularly during the critical postpartum period, can encourage positive nurse-patient rapport, strengthen parent-infant bonding, and promote continued substance use treatment beyond pregnancy.…”
Section: Discussionmentioning
confidence: 99%